2015
DOI: 10.1155/2015/597841
|View full text |Cite
|
Sign up to set email alerts
|

Research and Correlation of Diagnostic Methods for Assessment of the State of Oil Filling in Cycloid Gearbox

Abstract: The paper describes the research in the area of the application of diagnostic methods for assessment of the state of oil filling in cycloid gearbox of robotic manipulator. The experiments were realized on request of the manufacturer of the cycloid gearbox. Primarily, the two different methods were compared: an induction, magnetic method with the use of measurement system Cosmos-Steel Dust Checker and an RTG method, XRF (X-ray fluorescent method, analyses with use of X-ray radiation). These analytical methods p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Some recent studies (Bekana et al 2015, Sejkorová andGlos 2017) found that the optimal oil change, for good engine performance, mainly depends on the performed tasks and on the oil quality. Recent studies have investigated the characteristics and wear of the oils used in the engine and in the transmission and hydraulic systems of the farm tractors, and new types of oil are now available, complying with the new engine and transmission requirements and with the environmental aspects (Baron et al 2015, Kosiba et al 2016, Kučera and Aleš 2017, also extending the intervals in the lubricant oil change. The equation of the ASABE Standard D497.7 for the engine oil consumption considered a service interval of 100 hours, while nowadays the recommended service interval is up to 500-700 hours, depending on the model and manufacturer´s recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies (Bekana et al 2015, Sejkorová andGlos 2017) found that the optimal oil change, for good engine performance, mainly depends on the performed tasks and on the oil quality. Recent studies have investigated the characteristics and wear of the oils used in the engine and in the transmission and hydraulic systems of the farm tractors, and new types of oil are now available, complying with the new engine and transmission requirements and with the environmental aspects (Baron et al 2015, Kosiba et al 2016, Kučera and Aleš 2017, also extending the intervals in the lubricant oil change. The equation of the ASABE Standard D497.7 for the engine oil consumption considered a service interval of 100 hours, while nowadays the recommended service interval is up to 500-700 hours, depending on the model and manufacturer´s recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Since its launch, through continuous development, this reducer has gone through several improvements and, in addition to the basic T series, there are also E, H, G, and M series available (Table 1). These bearing reducers are used in combination with servomotors and are applied where high kinematic accuracy, high rigidity, backlash-free operation, and high torque capacity are required [1].…”
Section: Introductionmentioning
confidence: 99%